The Implementation of Strategic Planning in Municipalities of Lithuania - Astrauskas, Algirdas; Stasiukynas, Andrius (International Journal of Criminology and Sociology, 2022)
This article is devoted to present a system of selected criteria created by the authors of this article and to describe the stages of implementation of strategic planning in municipalities of Lithuania into which, based on this system of selected criteria, the authors of this article have proposed to divide the period from 1990 to the present day. The division of the period of implementation of strategic planning in municipalities of Lithuania chosen based on selected criteria and the characterisation of the processes taking place during those stages allows this article to be seen as scientifically new and relevant as well as useful in terms of transferring good practice.